Insights into Village Fund Management: Exploring Independence and Effectiveness - Setiawan, Heru Dian; Zulmasyhur, Zulmasyhur (Jurnal Manajemen Pelayanan Publik, 2024)
This research evaluated the Independence and Effectiveness of Fund Management in Prayungan Village, Bojonegoro Regency, in 2018-2022. Then, the research method adopted was quantitative descriptive. Then, the analysis of Village Financial Independence found that the average reached 96.6%, which can be categorized as high. Meanwhile, in the aspect of Village Financial Effectiveness, the figure obtained was 103.8%, indicating that managing village funds is very effective. In detail, Village Financial Independence indicates that Prayungan Village has a high level of independence regarding its financial resources and low dependence on external funds. Apart from that, Village Financial Effectiveness shows that the village can plan and realize the use of village funds very well. Overall research results show that the Prayungan Village Government (Pemdes) of Bojonegoro Regency is considered capable of managing village funds, which has high independence in internal financial resources along with aspects of the effectiveness of good management of village funds; this indicates the village's ability to manage and utilize funds. Village optimally during the research period. These findings have positive implications for development and community welfare in Bojonegoro Regency.